Spiritual care in Swedish prisons: Practices and experiences of spiritual caregivers - Bodin-Hadžibulić Sabina (Filozofija i Društvo, 2025)
This study focuses on spiritual care and how it is practised and experienced by spiritual caregivers in Swedish prisons. Its goal is to understand how prison conditions of different security classes affect spiritual care practice and what strategies spiritual caregivers use to help prisoners create and maintain their religiosity. The study uses five semi-structured interviews with prison spiritual caregivers from different religious traditions in various Swedish regions. To understand their experiences and practices, the concept of lived religion is applied. Analysis shows that the prison context strongly influences spiritual care practices, especially isolation and strict rules of behaviour and interpersonal interaction. Usually, spiritual care is provided through individual and group conversations. Religious rituals, services, and reading of religious texts occur to a lesser extent. However, spiritual care practices often transcend religious boundaries and have a transformative role in inmates’ lives.